Nitrergic and Substance P Immunoreactive Neurons in the Enteric Nervous System of the Bottlenose Dolphin (Tursiops truncatus) Intestine - Bombardi, Cristiano (Animals (Basel), 2021)
SIMPLE SUMMARY: The gastrointestinal tract of the bottlenose dolphin (Tursiops truncatus) differs structurally and functionally from that of terrestrial mammals. In particular, the intestine does not show any macroscopic subdivision and lacks a caecum. In addition, the histological aspect of the intestine is relatively constant, without marked differences between the anterior and posterior parts. Although the intestine of these cetaceans presents differences in comparison with terrestrial mammals, little information is currently available on their enteric nervous system. The aim of the present study was to investigate the morphological and quantitative aspects of neurons immunoreactive (IR) for the neuronal nitric oxide synthase (nNOS) and Substance P (SP) in the intestine of bottlenose dolphins (Tursiops truncatus). In these dolphin specimens, a smaller number of nNOS-IR neurons in the submucosal plexus and a larger number of SP-IR neurons in the myenteric plexus were observed compared to other mammals. Interestingly, no co-localization between nNOS- and SP-IR neurons was detected in either of the plexuses, suggesting the existence of two completely distinct functional classes of neurons in the intestine of the bottlenose dolphin. ABSTRACT: Compared with other mammals, the digestive system of cetaceans presents some remarkable anatomical and physiological differences. However, the neurochemical features of the enteric nervous system (ENS) in these animals have only been described in part. The present study gives a description of the nitrergic and selected peptidergic systems in the myenteric plexus (MP) and submucosal plexus (SMP) of the intestine of the bottlenose dolphin (Tursiops truncatus). The distribution and morphology of neurons immunoreactive (IR) for the neuronal nitric oxide synthase (nNOS) and Substance P (SP) were immunohistochemically studied in formalin-fixed specimens from the healthy intestine of three animals, and the data were compared with those described in the literature on other mammals (human and non-human). In bottlenose dolphins, the percentages of nitrergic neurons (expressed as median and interquartile range—IQR) were 28% (IQR = 19–29) in the MP and 1% (IQR = 0–2) in the SMP, while the percentages of SP-IR neurons were 31% (IQR = 22–37) in the MP and 41% (IQR = 24–63) in the SMP. Although morphological features of nNOS- and SP-IR neurons were similar to those reported in other mammals, we found some noticeable differences in the percentages of enteric neurons. In fact, we detected a lower proportion of nNOS-IR neurons in the SMP and a higher proportion of SP-IR neurons in the MP compared to other mammals. To the best of the authors’ knowledge, this study represents the first description and quantification of nNOS-IR neurons and the first quantification of SP-IR neurons in the intestine of a cetacean species. As nNOS and SP are important mediators of intestinal functions and the nitrergic population is an important target for many neuroenteropathies, data obtained from a healthy intestine provide a necessary basis to further investigate and understand possible functional differences and motor intestinal dysfunctions/alterations in these special mammals.